Fotopletismografia na mensuração da pressão arterial sistólica de cadelas anestesiadas - Vaccarin, Charline Vanessa (2021)
The objective was to evaluate and compare the use of photoplethysmography with the Doppler Vascular method, as an indirect method of measuring systolic blood pressure in bitches submitted to elective ovariohysterectomy. Thirty-four healthy bitches received meperidine (4 mg / kg, IM), followed by anesthetic induction with fentanyl (2.5 μg/kg, IV) and propofol (4 mg / kg, IV), maintaining general anesthesia with isoflurane diluted in 100% oxygen, and intraoperative analgesia with fentanyl (5 μg/kg/h, IV). They were randomly allocated between thoracic limb (TL) and pelvic limb (PL) groups, referring to the region in which noninvasive systolic blood pressure (NSP) was measured using vascular Doppler (DOP) and photoplethysmography (PPG), simultaneously. Their values were compared with those obtained invasively (ISP), through cannulation of the auricular artery. A strong correlation was obtained (r² = 0.95) between the DOP and PPG methods regardless of the limb to which the sensors were allocated. The low correlation between ISP and NSP was noted for both methods. The DOP and PPG methods showed greater agreement (r2 = -0.0061; p = 0.85) between them in the TL group. In this study it was found that the best measurement site using non-invasive methods is the thoracic limb. It is concluded that the non-invasive methods demonstrate low correlation with the ISP, however, it was observed that both demonstrate similar behavior, being able to use the photoplethysmographic method in substitution to the vascular Doppler method.